Teori Kognitif Sosial Albert Bandura (Studi Kritis Dalam Menjawab Problem Pembelajaran di Mi) - Elga Yanuardianto (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Discussion on the theory of conditioning (behaviorism) which succeeded in the field of learning during the first half of the twentieth century. Beginning in the late 1950s and early 1960s these theories were questioned in many fields. The influence of these theories is decreasing, and currently the more prominent theoretical perspectives are cognitive perspectives. One of the major challenges to behaviorism comes from observational learning studies conducted by Albert Bandura and his colleagues. The most important finding of this research is that people can learn new actions just by watching others do it. The observer does not have to carry out these actions when he learns them. Strengthening is not necessary so learning can occur. These findings refute the central assumptions of conditioning theories. Social cognitive theories that highlight the idea that most human learning takes place in a social environment. By observing others, people acquire knowledge, rules, skills, strategies, beliefs and attitudes. In learning in social cognitive MI, it is important to apply considering that children of this age do a lot of learning from observing the surrounding environment, both observing teachers, parents, and the community as a model, so it is important to create a good environment in learning MI age.Keywords: Social Cognitive Theory, Learning